2006
DOI: 10.1021/ja060499i
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Enantiopure β-d-Mannosyl Phosphomycoketides from Mycobacterium tuberculosis

Abstract: The first stereoselective total synthesis of a beta-d-mannosyl phosphomycoketide is reported. To introduce the stereogenic centers in the chain, three linear chiral building blocks were prepared using two different asymmetric catalytic conjugate addition protocols. Coupling of the various linear fragments was affected using a Julia-Kocienski sequence. This approach constitutes a general and convergent method for the construction of saturated oligoisoprenoid chains of any length and stereochemistry. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 12 publications
2
57
0
1
Order By: Relevance
“…[177] Ein weiteres Beispiel für die Vielseitigkeit dieser katalytischen Methode ist die Totalsynthese von zwei im Mycobacterium tuberculosis natürlich vorkommenden Verbindungen. [178,179] Weiterhin wurden konjugierte Additionen von Dialkylzinkreagentien an cyclische stickstoffhaltige Michael-Akzeptoren wie die Lactame 72 und die Piperidone 74 beschrieben (Schema 21 a und b). [180,181] [183] Die Addition von weniger reaktivem Dimethylzink an die von Chalkon abgeleiteten, a,b-ungesättigten (Pyridyl)sulfonylimine 81 wurde ebenfalls untersucht (Schema 24 a).…”
Section: Abfangen Von Reaktionszwischenstufen Mit Elektrophilenunclassified
“…[177] Ein weiteres Beispiel für die Vielseitigkeit dieser katalytischen Methode ist die Totalsynthese von zwei im Mycobacterium tuberculosis natürlich vorkommenden Verbindungen. [178,179] Weiterhin wurden konjugierte Additionen von Dialkylzinkreagentien an cyclische stickstoffhaltige Michael-Akzeptoren wie die Lactame 72 und die Piperidone 74 beschrieben (Schema 21 a und b). [180,181] [183] Die Addition von weniger reaktivem Dimethylzink an die von Chalkon abgeleiteten, a,b-ungesättigten (Pyridyl)sulfonylimine 81 wurde ebenfalls untersucht (Schema 24 a).…”
Section: Abfangen Von Reaktionszwischenstufen Mit Elektrophilenunclassified
“…Compound 2 may be accessed via the assembly of two fragments 3 and 4 employing a dithiane coupling strategy (27)(28)(29)(30)(31). Both 3 and 4 are available from the ␣,␤-unsaturated thioesters 5 and 6 (11)(12)(13), each with a different alcohol protecting group to allow selective deprotection in later stages of the synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, Qi et al (5) reported the purification of a Phytophthora mating hormone and revealed that the structure consists of an array of 1,5-stereogenic centers. Such structures can in principle be accessed by our recently developed powerful methodology of catalytic enantioselective conjugate addition of Grignard reagents (6)(7)(8)(9)(10)(11)(12)(13)(14) (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Pfaltz group did not describe an iterative approach for the construction of polydeoxypropionates, their findings elegantly demonstrate an approach for the construction of 1,5-polymethyl structures. These occur in polypropionates from Mycobacterium tuberculosis 53 as well as in many isoprenoids.…”
mentioning
confidence: 99%